An Analysis of Nepalese Youth Understanding Level on Climate Change - Devkota, Niranjan; Phuyal, Ram Kumar (Asian Journal of Economic Modelling, 2017)
This study aims to analyze the level of understanding about climate change among the Nepalese youth. Perceptions regarding the knowledge about climate change, climate change indicators, impact made by such change, government intervention and various climate change policies were investigated. The exploratory survey was conducted with the help of self-administered questionnaire. A total of 954 youth studying at the different levels were selected purposively from about 2 dozens of schools and colleges that represent 4 different Universities, Higher Secondary and Schools in different areas of Kathmandu Valley. Both descriptive as well as inferential statistics were applied to analyze the data. The logistic regression model was used to test the hypothesis. The model prepared 5 different hypotheses to identify the actual level of youth understanding about climate change. The study results that 98% youth are aware about climate change. Similarly, the logit model revealed that youth are well aware of climate change since factors like study level, age, gender, formal education about climate change, participation in various climate-related training, climate change talk on family and society, access to mobile phone and use of mobile phone for climate change learning are found to be statistically significant at desirable probability level. However, in spite of youth awareness on climate change, still, they are unknown about the coping strategies such as adaptation and mitigation implemented by the government. It indicates government should transmit similar information via all possible channels to the youth so that the plan and policies that are related to climate change can be successfully implemented.